Prison Overcrowding and Harsh Conditions: Health and Human Rights Concerns to Persons in Custody, Staff, and the Community - Baffour, Frank Darkwa (Criminal justice and behavior, 2024)
The article explored overcrowding in Ghana prisons and sought to understand its impact on the health and well-being of persons in custody and prison officers. Qualitative data from 38 participants who were serving terms or working in three prison facilities in Ghana revealed three themes, including (a) fear over the spread of communicable diseases, (b) limited access to basic resources, and (c) psychological and emotional burden, attributing them to overcrowding in the prisons. We discussed the findings from human rights and prison and public security perspectives and concluded that addressing overcrowding in prisons would ensure a healthy prison environment, which may have implications for the well-being and human rights of persons in custody, as well as public safety and the health of prison officers and the community. To achieve a healthy prison, policies should target prison depopulation and commitment from stakeholders to implement local and international prison rules and conventions.